Analisis Perilaku Bullying dan Dampak Terhadap Kesehatan Mental Siswa di Madrasah Ibtidaiyah (MI) Istiqomah Pekanbaru - Anugrasia Auliani (SEHATI: Jurnal Kesehatan, 2026)
This study aims to analyze the forms of bullying behavior and their impact on students’ mental health in the Madrasah Ibtidaiyah environment. This research is specifically conducted within the context of MI Istiqomah Pekanbaru as the educational setting that serves as the focus of the discussion. The study employs a qualitative approach using a literature review method. Data were collected through a systematic examination and analysis of relevant scientific sources, including reference books, national and international journal articles, and previous studies addressing bullying and mental health issues among school-aged children.The findings indicate that the most common forms of bullying in madrasah settings include verbal, physical, and psychological bullying. The impacts of bullying on students’ mental health include feelings of fear, anxiety, stress, decreased self-confidence, and reduced learning motivation. The study also reveals that bullying prevention efforts can be implemented through character education based on Islamic values, strengthening the role of teachers as educators and role models, and fostering collaboration between madrasahs and parents. This study is expected to serve as a conceptual reference for madrasahs in formulating bullying prevention strategies and in creating a safe, comfortable, and conducive learning environment